Benefits of dense labour markets - Evidence from transitions to employment in Germany - Annekatrin Niebuhr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Agglomeration economies may impact on productivity in different ways. Up to now, only a few papers try to provide evidence on the underlying mechanisms that might give rise to a positive correlation between agglomeration and wages. In this analysis we focus on the matching mechanism, i.e. the hypothesis that the size of the local labour market allows for better matching of job seekers and vacancies. Better matches in turn are supposed to give rise to higher productivity. We aim at providing new evidence on the importance of the matching mechanism and investigate the effects of the density of local labour markets on the wages of new employment relationships. The analysis is based on a large micro data set that offers detailed information on labour market biographies of workers in Germany. We apply the two-stage regression approach proposed by Combes et al. (2008) and distinguish between different types of transition, i.e. job-to-job transitions as well as transitions from shor tand long-term unemployment. The results point to rather small positive effects on productivity: a doubling of the employment density increases the productivity of new employment relationships by 1.1% to 1.4%. Moreover, the findings indicate that the benefits of a better match might only accrue to persons with a job-to-job transition as well as short-term unemployed. We detect no important impact of agglomeration for transitions from long-term nonemployment.
Keywords: J31; R23; C23; 330